PENINGKATAN PEMAHAMAN INTELEKTUAL SISWA SD MELALUI VIDEO ANIMASI INTERAKTIF BERBASIS MEDIA DIGITAL DAN PROYEKTOR DI SD - Warni Ani; Ananda Amelia; Srinovita Srinovita; Evianti Theresa Osimpu; Theopilus Motoh (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Primary education plays a crucial role in establishing students’ cognitive foundations, including logical reasoning, conceptual understanding, and critical thinking skills. However, teaching and learning processes at this level often face challenges, particularly in delivering materials in a way that is engaging and aligned with children's learning styles. To address these issues, this community service activity aimed to enhance students’ intellectual understanding by integrating interactive animated videos projected through digital media. The activity took place on July 15, 2025, at SD Negeri 1 Nalu, involving 33 sixth-grade students. The instructional content focused on the theme of environmental preservation within the IPAS (Science and Social Studies) subject. A participatory approach was employed, including teacher training, pre- and post-tests, animated video presentations, and interactive discussions. The results showed a significant increase in students’ comprehension, as evidenced by higher post-test scores. Students also demonstrated enthusiasm and active participation throughout the learning process. In conclusion, the integration of projector-based interactive animation proves to be an effective instructional strategy, enhancing not only students’ conceptual grasp but also fostering early awareness of environmental responsibility.